Matthew 9: 9-17 and the Divine Bridegroom of Hosea - Eagy, Ryan (The expository times, 2017)
Jesus's use of the bridegroom imagery is usually connected to the divine bridegroom in the OT through systematic or biblical theological categories. This article argues that Matthew's use of Hosea 6:6 in Matt 9:13 is an indicator that readers should understand Jesus's bridegroom metaphor in Matt 9:15 as a claim to occupying the same role as the divine bridegroom of Hos 2:16. By following two lines of reasoning--the unity of Matt 9:9-17 and the literary and textual connections between Hos 6:6 and Hos 2:16--this paper will seek to demonstrate this high Christological claim was intentional in Matthew's account.